2009
DOI: 10.1016/j.rvsc.2009.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Molecular screening and risk factors of enterotoxigenic Escherichia coli and Salmonella spp. in diarrheic neonatal calves in Egypt

Abstract: The aim of the present study was to carry out molecular epidemiological investigation on enterotoxigenic Escherichia coli (ETEC) K99 and Salmonella spp. in diarrheic neonatal calves. Fecal samples were obtained from 220 diarrheic calves at 9 farms related to four governorates in central and northern Egypt. E. coli and Salmonella spp. isolates were examined for E. coli K99 and Salmonella spp. using PCR. ETEC K99 was recovered from 20 (10.36 %) out of 193 isolates, whereas Salmonella spp. was recovered from nine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
24
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 39 publications
(42 reference statements)
15
24
1
Order By: Relevance
“…In the present study, 53 of 345 isolates carried the f5 (36 isolates) and f41 (17 isolates) genes, and all of the F5-positive strains isolated from diarrheic calves were less than 7-day old. The susceptibility of the calves to ETEC in this age period is in agreement with previous reports [21,38]. Interestingly, in this study, we found that none of the F5-positive strains encoded enterotoxin genes (STa) when analyzed by PCR and they were also negative when tested with baby mice (data not show).…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, 53 of 345 isolates carried the f5 (36 isolates) and f41 (17 isolates) genes, and all of the F5-positive strains isolated from diarrheic calves were less than 7-day old. The susceptibility of the calves to ETEC in this age period is in agreement with previous reports [21,38]. Interestingly, in this study, we found that none of the F5-positive strains encoded enterotoxin genes (STa) when analyzed by PCR and they were also negative when tested with baby mice (data not show).…”
Section: Discussionsupporting
confidence: 93%
“…Totally, the prevalence of E. coli strains isolated from calves with diarrhea in Iran (76.45%, our results) was significantly higher than Egypt (10.36%) [37] and India (42.65%). Mora et al [38] reported that 12% of the calves and 22% of the farms samples were positive for highly virulent STEC serotype O157:H7.…”
Section: Resultsmentioning
confidence: 46%
“…Pathogenic E. coli strains have different virulence factors that allow them to colonize the host's small intestine, avoiding the immune response and stimulating the deleterious inflammatory response to produce diarrhea 11,45 . These virulence factors include the antigens of colonization or adhesion (F2---F6, F17, F18, F41 fimbriae and intimin) and exotoxins (heat-labile enterotoxin [LT], heat-stable enterotoxins [STa and STb] and verotoxins [VT]) 26 .…”
Section: Escherichia Coli;mentioning
confidence: 99%
“…Farm animal and human diarrhea are frequently due to infection by one or several of E. coli pathotypes: enterotoxigenic E. coli (ETEC), enteropathogenic E. coli (EPEC), enteroinvasive E. coli (EIEC), Vero toxin-producing/Shiga toxin-producing E. coli (VTEC/STEC) which include its well-known subgroup enterohemorrhagic E. coli (EHEC), enteroaggregative E. coli (EAggEC) and enteroadherent E. coli (EAdEC) 28 . ETEC infection is the most common type of colibacillosis in young animals especially in calves and piglets 45 .…”
Section: Escherichia Coli;mentioning
confidence: 99%